Parties Matter in Allocating Expenditures: Evidence from Germany - Niklas Potrafke (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
I test if parties matter with respect to the allocation of public expenditures in Germany. Considering the allocation of rights and duties due to the federal structure, two econometric models are estimated. First, a SURE model analyses spending at the federal level for the period from 1950 to 2003 and finds evidence for partisan politics and election year effects. Second, I examine the spending behaviour in the states from 1974 to 2004 in a panel data framework. In comparison to the federal level, policy has weaker impacts on the allocation of expenditures in the states.
Keywords: H72; H50; D72; 330; allocation of public expenditures; partisan politics; fiscal federalism